Il ruolo della Chiesa spagnola nel processo di transizione democratica: una lettura attraverso i documenti episcopali - Abu Salem, Miriam (Il diritto ecclesiastico, 2022)
The role of the Spanish Church in the democratic transition process. A reading through the episcopal documents · The essay analyzes the relationship between the Spanish Catholic church and the State during Francoist dictatorship. In particular, the paper focuses on the role played in the consolidation and de-legitimization process of Francoism by the Spanish clergy, through the analysis of some episcopal documents.